Implementation of the Halal Thoyib Principle in Beef Consumption (A Case Study of the Muslim Community in Tembung Village) - Agustami Daulay; Muhammad Lathief Ilhamy Nasution; Waizul Qarni (Islamic Economics and finance in Focus, 2026)
This study aims to analyze the implementation of the halal thoyib principle in beef consumption among the Muslim community of Tembung Village. The halal thoyib principle is a fundamental concept in Islam that emphasizes not only the legality of food according to Islamic law, but also its wholesomeness, cleanliness, safety, and health aspects. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with six informants consisting of consumers and beef sellers, supported by field observations. The findings indicate that the community prioritizes the halal aspect in beef consumption, particularly regarding Islamic slaughtering practices and trust in Muslim sellers. However, the thoyib aspect has not been comprehensively understood or fully implemented. The community tends to perceive thoyib merely as the physical freshness of meat, with limited attention to sanitation, hygiene, and post-slaughter handling. Social trust and religiosity play a significant role in shaping consumption behavior, while limited knowledge and facilities hinder the optimal implementation of the halal thoyib principle. This study concludes that the implementation of the halal thoyib principle in beef consumption in Tembung Village remains partial, highlighting the need for continuous education and assistance to enhance public awareness of holistic halal and thoyib food consumption.